Minimizing Academia vs. Industry Conflict Through Identification of Common Test Models’ Process Areas and Maturity Levels’ Variations (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2020)
The quality of developed software is highly influenced by the quality of the development process. Testing process, as a stage in software development, especially, contributes to software quality. However, testing process requires significant effort and has been in the focus of both academia and practice. As a result, many test process models have been developed. Problems arise, because of gap between academia and practice. Some models are just on a conceptual level, others do not take into account needs of the industry; some models are general, while others are domain specific. One research has also shown that many models lack assessment tools. The main objective of this paper is to minimize the gap between industry and academia by comparing test process models and determining common test process activities and variations in maturity models. To accomplish this, three scientific databases were chosen for conducting primary research: Springer Link, Science Direct and IEEE xplore. Search string structured in the form of “test process model” was applied in the above stated databases. Springer Link search resulted in 129 hits; Science Direct search gave 139 hits, while IEEE xplore search resulted in 15 hits. One of the resulting papers reported 23 test process models and standards, so secondary search was conducted as well. All available models (from primary and secondary search), were then compared. Maturity levels and process areas were extracted. Differences in maturity levels, as well as common activities for available test process models have been identified and presented, with the purpose of bridging the gap between industry and academia and thus increasing the quality of testing processes in software organizations, since higher quality of testing will lead to higher quality software.